Конституционализм в исламских государствах : становление, современное состояние и направления трансформации - Бехруз, Хашматулла Набиевич; Бехруз, Хашматулла Набієвич; Behruz, Hashmatulla (My University, 2012)
The article details the phenomenon — the Islamic Constitutionalism and its forming, process of evolution and current status. Particular attention is paid to the modern trends of its transformation in the context of the ongoing processes in the modern Islamic countries.
Бехруз Х. Н. Конституционализм в исламских государствах : становление, современное состояние и направления трансформации / Х. Н. Бехруз // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 261-271.
Keywords: исламский конституционализм; исламское право; исламская правовая система; правовые системы современных исламских государств; конституция; трансформация; ісламський конституціоналізм; ісламське право; ісламська правова система; правові системи сучасних ісламських держав; конституція; трансформація; islamic constitutionalism; Islamic law; Islamic legal system; legal system of modern Islamic states; the constitution; the transformation